Quality of employment in times of transformation: the case of private agricultural salaried workers of Uruguay between 2004 and 2019 (PAMPA, 2026)
This work aims to observe and analyze the evolution of the quality of employment of private agricultural wage earners in Uruguay between 2004 and 2019; a period characterized by profound transformations in the agricultural sector and institutional changes in the workplace. To measure the evolution of the quality of employment, the “Bad Jobs Index” (IME) is used, a synthetic index composed of four dimensions: social security, productivity, income and working hours. In summary, the results show a gradual improvement in the quality of employment, however, given the context, this improvement does not seem to be enough; There are still pending challenges to achieve a substantial and equitable improvement in working conditions in other productive sectors.
Keywords: Employment Quality; Agricultural Wage Earners; Agricultural Transformations